The Influence of Work From Home, Workload and Work Environment On Employee Performance - Dian Nanda Putri Aspita; Primasatria Edastama (Universitas Nusantara PGRI Kediri, 2023)
The work from home policy implemented by the company will have an impact on changes in work patterns and performance of its employees. Where in these changes there is a good influence and opposite effect for the company. The purpose of this study is to explore the correlations between work from home, workload and work environment in impacting employee performance. In the sampling process, this research used a non-probability sampling method based on purposive sampling with the determination of the number of samples using the formula from Yamane, so that there were 139 respondents who were sampled in this study. The results of the research explained that working from home give a positive impact on employee performance, workload give a negative impact on employee performance, and employee environment give a positive impact on employee performance. The data analysis method used in this research used multiple linear regression analysis test. Therefore, it hoped that firm management will be able to fully implement work-from-home rules by assigning workloads that are compatible with employee capacity and making sure that the workspaces and tools used by employees when working from home are suitable.